La transformación del paisaje urbano-rural en el municipio de Montenegro, Quindío. - Cifuentes Monsalve, Diana Marcela; Duque Arango, Gloria Inés (Revista: Módulo Arquitectura CUC)
The recognition of the Coffee Cultural Landscape has promoted the development of the region with a cultural and ecological approach. However, the Municipality of Montegro presents a rural urban transformation, around its main attraction, the Parque del Café. This article aims to present the case study of the rural urban transformation of the municipality of Montenegro (Quindío, Colombia), which is part of a series of changes under a tourism model around the Coffee Cultural Landscape. The analysis is developed under the qualitative methodology, where cartography becomes the main tool. This makes it possible to establish a cross-section of information, between plans, maps and observations that reveal the transformation of rural land and public space in the urban area, that is, the rural urban heritage as an object of consumption for cultural tourism.